Guinea : Request For A Three-Year Arrangement Under The Extended Credit Facility-Press Release; Staff Report; and Statement by the Executive Director for Guinea. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2017)
This paper discusses Guinea's Request for a Three-Year Arrangement Under the Extended Credit Facility (ECF). The Guinean economy has rebounded from the adverse impact of the Ebola epidemic, and growth is expected to continue to be sustained supported by buoyant mining activity and the scaling-up of infrastructure investments. The three-year ECF arrangement will help Guinea address a protracted balance of payment need and implement economic policies and reforms to foster higher and broad-based growth. The program will also play a catalytic role in mobilizing donor financing, notably from the World Bank and the European Union.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet